2018
DOI: 10.3389/fnins.2018.00599
|View full text |Cite
|
Sign up to set email alerts
|

Cortical Surface Area Rather Than Cortical Thickness Potentially Differentiates Radiation Encephalopathy at Early Stage in Patients With Nasopharyngeal Carcinoma

Abstract: Radiation encephalopathy (RE) is one of the most severe complications in nasopharyngeal carcinoma (NPC) patients after radiotherapy (RT). However, the morphological alteration of early RE is insufficiently investigated. We aimed to investigate the cortical thickness and surface area alterations in NPC patients with or without RE in the follow-up. A total of 168 NPC patients each underwent a single scan and analysis at various times either Pre-RT (n = 56) or Post-RT (n = 112). We further divided the Post-RT NPC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(37 citation statements)
references
References 51 publications
3
33
1
Order By: Relevance
“…In comparison with the pre-RT group, we found significantly decreased LGI in the bilateral STG/MTG in NPC patients treated with CCRT. These findings are in line with previous structural studies, which reported significant alterations in GM volume, cortical surface area, and cortical thickness in NPC patients following their treatment (6, 11, 13, 14). Some DTI studies also provided evidence of WM damage in NPC patients following treatment (7, 15, 30), as reflected by altered fractional anisotropy (FA) and/or mean diffusivity (MD) in the temporal lobes.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In comparison with the pre-RT group, we found significantly decreased LGI in the bilateral STG/MTG in NPC patients treated with CCRT. These findings are in line with previous structural studies, which reported significant alterations in GM volume, cortical surface area, and cortical thickness in NPC patients following their treatment (6, 11, 13, 14). Some DTI studies also provided evidence of WM damage in NPC patients following treatment (7, 15, 30), as reflected by altered fractional anisotropy (FA) and/or mean diffusivity (MD) in the temporal lobes.…”
Section: Discussionsupporting
confidence: 93%
“…The inclusion criteria for all patients in this study were as follows: (1) Pathologically confirmed NPC patients; (2) normal-appearing brain parenchyma on MRI; (3) right-handedness; (4) more than 6 years of education; and (5) an age range from 20 to 60 years. Exclusion criteria included patients with brain parenchymal invasion, brain tumors, prior substantial head trauma or surgery, neurological or psychiatric diseases, alcoholism or drug abuse, or any other major intracranial disease (6). The diagnostic criteria for RE included the following three aspects: a history of NPC with RT, typical MRI findings in the temporal lobes, and exclusion of other intracranial disease (Figure S1).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present study, two genetically and phenotypically independent morphological indices, namely cortical thickness and cortical surface area, were adopted to assess the alterations in cortical structure (Hogstrom, Westlye, Walhovd, & Fjell, ; Panizzon et al, ; Rakic, ; Rimol et al, ; Zhang et al, ; Zhang et al, ). Because each index measures a unique aspect of cortical morphology, analyzing them separately might help uncover the neural mechanisms involved in the development of DPN.…”
Section: Discussionmentioning
confidence: 99%